German Corporate Governance in International and European Context - Plessis, Jean J. du. author. aut Link
XIV, 276 p.
Keywords: The global economy brings us into a new world of legal players and legal transac- 1 tions. Corporations from many countries and divergent cultural backgrounds - come our partners for business and investment. Therefore, it is indispensable to know the main principles of other countries’ corporate governance structures. Some remarkable developments have taken place in the European Union (EU) in recent times: the EU now comprises 27 Member States after Cyprus and several other Eastern and Southeastern European States became members in 2004 and with Romania and Bulgaria joining the EU in January 2007. Company law h- monisation is once again high on the agenda of the EU; the first European C- panies (SE) started to do business at the end of 2004; and every day more and more cross-border trade takes place within the EU. This book aims to provide the reader with a basic understanding of the German corporate governance system. It offers an overview of German corporations law and explains the interrelationship among the various organs required for German public corporations. It also gives an overview of recent corporate governance - velopments in Germany. The German system of employee codetermination and its future is dealt with in detail, while we also focus on accounting as the docum- tary proof of good corporate governance.